MODERN METHODS OF CONTROLLING WOUND HEALING AFTER FISTULIZING GLAUCOMA SURGERY. ANTI-INFLAMMATORY DRUGS AND NEW TRENDS - S. Yu. Petrov (Oftalʹmologiâ)
The  article  describes  modern approaches  for  controlling  wound  healing  after  fistulizing  glaucoma   surgery.  The  review  recounts international experience of steroidal and nonsteroidal anti-inflammatory drug and their efficacy research study results. Much attention is given to new strategies of wound healing regulation  after  fistulizing glaucoma  surgery, aimed  at  enhancing  its results. The article describes characteristics and modes of action of medicinal agents effecting the cytoskeleton, such as Rho-kinase inhibitors and taxane anticancer agents. A detailed account of modes of effecting wound healing through  regulating  the process growth factors, proteinases and cytokines  is also given. Possible  strategies include antifibrotic cytokine interferon-α  application and inhibiting the following agents: transforming growth  factor β; connective tissue growth  factor (CTGF), that  controls  extracellular  matrix components production  and cicatrical  tissue formation; vascular  endothelial  growth  factor (VEGF), that  indirectly influences  fibrotic activit y through  its angiogenic effect and also has  a supposed direct  effect on fibroblast activit y; proinflammatory placental  growth factor (PIGF), that  increases  bleb area size and  its survival time,  and  decreases postoperative  angiogenesis, inflammation  and  fibrosis  intensit y.  The last  part  of the article gives a brief report on less  widespread and researched methods of wound healing regulation, such  as  suppressing the activit y of matrix metalloproteinases and amniotic membrane application.